Camelina Seed Supplementation at Two Dietary Fat Levels Change Ruminal Bacterial Community Composition in a Dual-Flow Continuous Culture System - Dai, Xiaoxia; Weimer, Paul J.; Dill-McFarland, Kimberly A.; Brandao, Virginia L. N.; Suen, Garret; Faciola, Antonio P. (Frontiers in Microbiology, 2017)
This experiment aimed to determine the effects of camelina seed (CS) supplementation at different dietary fat levels on ruminal bacterial community composition and how it relates to changes in ruminal fermentation in a dual-flow continuous culture system. Diets were randomly assigned to 8 fermenters (1,200-1,250 mL) in a 2 × 2 factorial arrangement of treatments in a replicated 4 × 4 Latin square with four 10-d experimental periods that consisted of 7 d for diet adaptation and 3 d for sample collection. Treatments were: 1) no CS at 5% ether extract (EE, NCS5); 2) no CS at 8% EE (NCS8); 3) 7.7% camelina seed at 5% EE (CS5); and 4) 17.7% CS at 8% EE (CS8). Megalac was used as a control to adjust EE levels. Diets contained 55% orchardgrass hay and 45% concentrate, and fermenters were equally fed a total of 72 g/d (DM basis) twice daily. The bacterial community was determined by sequencing the V4 region of the 16S rRNA gene using the Illumina MiSeq platform. Sequencing data were analyzed using mothur and statistical analyses were performed in R and SAS. The most abundant phyla across treatments were the Bacteroidetes and Firmicutes, accounting for 49% and 39% of the total sequences, respectively. The bacterial community composition in both liquid and solid fractions of the effluent digesta changed with CS supplementation but not by dietary EE. Including CS in the diets decreased the relative abundances of Ruminococcus spp., Fibrobacter spp., and Butyrivibrio spp. The most abundant genus across treatments, Prevotella, was reduced by high dietary EE levels, while Megasphaera and Succinivibrio were increased by CS supplementation in the liquid fraction. Correlatively, the concentration of acetate was decreased while propionate increased; C18:0 was decreased and polyunsaturated fatty acids, especially C18:2 n-6 and C18:3 n-3, were increased by CS supplementation. Based on the correlation analysis between genera and fermentation end products, this study revealed that CS supplementation could be energetically beneficial to dairy cows by increasing propionate-producing bacteria and suppressing ruminal bacteria associated with biohydrogenation. However, attention should be given to avoid the effects of CS supplementation on suppressing cellulolytic bacteria.